Public Speaking Training at SMKN 1 Slawi - Permadi, Didi; Florina, Ike Desi; Hartati, Oemi; Edy, Sarwo (ASEAN Journal of Empowering Community, 2022)
One element most important from life socializing is interacting with other people. A person's verbal ability becomes very important because talking to other people will knowing ability someone and can rate it or know with term Public speaking. The phenomenon that happened  Moment this many held open Public speaking training for general or organized by the agency or school. Public speaking training shows existence needs will reference base for understanding basics speaking in front of general like at the start of the heyday rhetoric. The UPS Tegal Service Team scheduled the implementation of public speaking training at SMKN 1 Slawi as a form of Devotion To the Community. Destination holding is to improve the skills and abilities of students/participants in public speaking so that they can be applied in life daily or later in the world of work. Implementation use method lecture ( gift ) materials and training directly (workshop), with target participants SMKN 1 Slawi students as many as 50 participants. mplementation condwas ucted two-dayday implementations. Output from devotion to Public this is mass media publication or rise journal devotion UPS Tegal community.